Effects of Computer-Assisted Instruction for Struggling Elementary Readers With Disabilities. (August 2014) - Regan, Kelley; Berkeley, Sheri; Hughes, Melissa; Kirby, Suzanne
Despite a lack of conclusive evidence, many researchers in the field view computer-assisted instruction (CAI) as an opportunity for improved instruction for students with disabilities. This study examined the effects of a CAI program, Lexia Strategies for Older Students (SOS)™ on the word recognition skills of four, upper elementary students with mild disabilities. This study used a multiple-probe design across three targeted reading skill conditions per student. Findings revealed that some students were able to meet mastery of basic word reading skills with Lexia SOS alone, while others needed additional direct instruction. Student perceptions of Lexia SOS were positive. Results have particular implications for instruction in classrooms beyond the primary grades (K-3) when the focus of the curriculum shifts away from basic decoding instruction. Directions for future research are discussed.